The courage to be herself: Daisy Miller unbowed - Jean-Rémi Lapaire; Raphaël Bzar (Miranda: Revue Pluridisciplinaire du Monde Anglophone)
We follow 11 English and Drama students from Université Bordeaux Montaigne as they travel to Vercelli, Piedmont, to perform Daisy Miller in the magnificent historic buildings of the Teatro Civico for the TiLLiT festival (Teatro in Lingua, Lingua in Teatro). They have created an inspiring stage version of Henry James' novella, combining theatrical and choreographic ingredients. The performers are aged 22-26 and have a strong generational connection to the brief destiny of a young “American girl” who wants to be herself in a society that strives to crush her will and control her morals. The director and the cast decide to reassign gender identities, create a tragicomic chorus and invent an apocalyptic epilogue. Daisy returns in radiant whiteness to lay at her feet the world that has so harshly and unfairly judged her.